Mitochondrial ROS regulate thermogenic energy expenditure and sulfenylation of UCP1 - Chouchani, Edward T.; Kazak, Lawrence; Jedrychowski, Mark P.; Lu, Gina Z.; Erickson, Brian K.; Szpyt, John; Pierce, Kerry A.; Laznik-Bogoslavski, Dina; Vetrivelan, Ramalingam; Clish, Clary B.; Robinson, Alan J.; Gygi, Steve P.; et al. (Nature (London), 2016)
Uncoupling protein 1 (UCP1)-dependent thermogenesis in brown adipose tissue is supported by a burst of mitochondrial reactive oxygen species upon cold exposure. Control of brown fat thermogenesis Thermogenic respiration in brown adipose tissue (BAT) and beige fat relies on the uncoupling protein 1 (UCP1), a mitochondrial inner membrane protein that produces heat by dissipating the mitochondrial proton gradient generated by the respiratory chain. These authors show that UCP1 activation is supported by a burst of mitochondrial reactive oxygen species (ROS) upon cold exposure. ROS are necessary to sulfenylate a critical cysteine residue in UCP1, which drives its activation — in effect, the 'on/off switch' for UCP1. Brown and beige adipose tissues can dissipate chemical energy as heat through thermogenic respiration, which requires uncoupling protein 1 (UCP1) 1 , 2 . Thermogenesis from these adipocytes can combat obesity and diabetes 3 , encouraging investigation of factors that control UCP1-dependent respiration in vivo . Here we show that acutely activated thermogenesis in brown adipose tissue is defined by a substantial increase in levels of mitochondrial reactive oxygen species (ROS). Remarkably, this process supports in vivo thermogenesis, as pharmacological depletion of mitochondrial ROS results in hypothermia upon cold exposure, and inhibits UCP1-dependent increases in whole-body energy expenditure. We further establish that thermogenic ROS alter the redox status of cysteine thiols in brown adipose tissue to drive increased respiration, and that Cys253 of UCP1 is a key target. UCP1 Cys253 is sulfenylated during thermogenesis, while mutation of this site desensitizes the purine-nucleotide-inhibited state of the carrier to adrenergic activation and uncoupling. These studies identify mitochondrial ROS induction in brown adipose tissue as a mechanism that supports UCP1-dependent thermogenesis and whole-body energy expenditure, which opens the way to improved therapeutic strategies for combating metabolic disorders.